Eksplorasi Pengalaman Guru dalam Mengimplementasikan Kurikulum Merdeka di SMA Ignatius Manado - Mentang, Paulus Joseph; Landaiyo, Wilson Y.; Mua, Marianus Muharli (Instructional Development Journal, 2025)
This study aims to explore teachers' experiences in implementing the Merdeka Curriculum at SMA Ignatius Manado, as well as to identify the challenges, strategies, and support needed for its successful implementation. Using a qualitative approach with a case study design, data were collected through in-depth interviews and participatory observations. Thematic analysis was employed to identify patterns and key themes in the teachers' experiences. The findings indicate that the main challenge faced by teachers is their readiness to adapt to more flexible, student-centered teaching methods, as well as limitations in resources and supporting facilities. To overcome these challenges, teachers at SMA Ignatius Manado have developed collaborative strategies, participated in training, and engaged students more actively in the learning process. The support needed to improve the implementation of the Merdeka Curriculum includes continuous training, provision of adequate facilities, and social support from various stakeholders. This research provides valuable insights into the dynamics of implementing the Merdeka Curriculum and offers recommendations to support its success in senior high schools.